Trabalho escravo contempor??neo no Maranh??o: an??lise da efic??cia da repress??o na Justi??a do Trabalho da 16?? Regi??o - Costa, Marcos S??rgio Castelo Branco (2016)
This dissertation aims at the analysis of the effectiveness of judicial repression of contemporary slave labor in Maranh??o through the judgments of the Labor Court of the 16th Region on the topic. As an initial step, it proves to be essential to examine the effectiveness of repression, characterize the contemporary slave labor, explaining the modern forms of slavery, its occurrence modes, the legally protected interests, especially dignity. Therefore, the main international instruments dealing with the issue were examined. The main rules were also studied the internal law, beginning with the Federal Constitution, stating, besides the characterization, the most important tools for combating slave labor. Passes to the qualitative and quantitative study of decisions handed down in actions to combat the repression of slave labor, such as public civil actions, both in the first and in the second instance and it is concluded that, in the first instance, the prosecution proves effective , which does not occur in the second instance, because it uses interpretations that restrict the range of incidence of contemporary slave labor.